Analysis of the effectiveness of using digital technologies in teaching first-year medical students - Popovуch, A. P.; Aliyeva, O. H.; Попович, Аліса Петрівна; Алієва, Олена Геннадіївна (My University, 2024)
The purpose of this study is to determine the most effective modern information technologies and the level of their effectiveness in the study of the subject "Medical Biology," as well as the attitude of students to their use and the impact on the ability to perceive educational material. Methodology. The study employed a complex set of research methods, including theoretical (such as analysis of scientific sources, pedagogical and teaching materials, and comparison) and empirical (such as summarizing teaching experience and interviewing) methods. First-year students (130) of the medical university were involved in the survey. Метою даного дослідження є інформаційних технологій та рівня їхньої ефективності під час вивчення предмета «Медична біологія», а також ставлення студентів до їхнього використання та впливу на здатність сприйняття навчального матеріалу. Методи. У дослідженні використано комплекс методів дослідження, серед яких теоретичні (аналіз наукових джерел, педагогічних та навчально-методичних матеріалів, порівняння) та емпіричні (узагальнення педагогічного досвіду та інтерв'ювання). В опитуванні були залучені студенти (130) першого курсу медичного університету.
Аналіз ефективності використання цифрових технологій у навчанні студентов-медиків 1-го курса
Keywords: educational process; mind maps; problematic lecture; virtual laboratories; віртуальні лабораторії; ментальні карти; освітній процес; проблемні лекції